The effectiveness of virtual program for developing social competence among Grade Seven’s students at private schools in Riyadh City - Alnamlah, Abdulrahman Suliman (Journal of Educational and Psychological Sciences, 2021)
This study aimed at determining effectiveness of virtual program for developing social competence among Grade Seven students at private schools in Riyadh City. The quasi-experimental method was used, and the study sample consisted of (n =27) participants, that were divided into two groups; the first was the experimental group and consisted of (17) students, and the second was the control group and consisted of (12) students. Then, a scale of Social Competence was used with the two groups, after testing its validity and reliability. The scale consisted of (25) items distributed into three dimensions; personal skills, academic skills and self-control. By using Microsoft teams, the virtual program for developing social competence was applied among the students of the experimental group. The study results showed a considerable effectiveness of the virtual program in developing social competence among the students of the experimental group, where the adjusted gain percentage for Blake was (2.24). The results also indicated significant differences (α ≥ 0.05) in social competence between means of the two groups and were for the students of the experimental group. The study ended up with a number of recommendations, most of which as follows:1. The necessity of using the proposed virtual training program in developing social competence among the middle school students; as it proved its great role, especially during the lockdown caused by Covid-19.2. It is recommended that the Ministry of Education makes use of the virtual program and trains teachers to acquire necessary training skills in order to develop social competence of their students.3. Apply the theories of active learning and participatory training with their its various strategies in the education process.
Keywords: Social Competence; Grade Seven; Virtual Program